Innovative financial instruments for natural disaster risk management - Andersen, Torben J. (IDB WashingtonUS, 2002)
Presents a general assessment of the potential for catastrophe risk transfer. Analyses different ways in which risk transfer can take place. Evaluates the future potential for a combination of conventional insurance approches and new alternative risk management instruments that can help private financial coverage for catastrophe risk exposures.